Thromboembolic safety of transdermal hormone therapy - Stachowiak, Grzegorz; Pertyński, Tomasz (Menopause Review/Przegląd Menopauzalny, 2008)
This article is a review of up-to-date reports – the newest references and own studies – on the influence of transdermal hormone therapy (HT) on thromboembolic risk in menopausal women. The available data testify clearly to the high thromboembolic safety of HT, even when this therapy is administered in women with thromboembolic risk factors.